Acute kidney injury in patients with idiopathic membranous nephropathy: influencing factors and prognosis. Issue 1 (31st December 2023) - Li, Zhenzhou; Weng, Mengjie; Lin, Lizhao; Chen, Yi; Lin, Jiaqun; Cui, Jiong; Jiang, Dewen; Fu, Binbin; Li, Guifen; Chen, Caiming; Xu, Yanfang; Wan, Jianxin
Abstract: Aim: Idiopathic membranous nephropathy (IMN) is a common type of nephrotic syndrome, and is associated with acute kidney injury (AKI). We investigated the association of multiple variables with AKI in patients with IMN. Methods: The data of 187 patients with biopsy-proven IMN were examined. Renal outcome was defined as progression to end-stage renal disease (ESRD). Binary logistic regression and Kaplan–Meier's analysis were used for statistical analysis. Results: During follow-up, 46 (24.6%) patients developed AKI. The incidence of AKI was greater in males than females ( p < .01). The AKI group had higher uric acid, lower serum PLA2R antibody positive, and worse baseline kidney function (all p < .01). Most patients in the AKI group had stage I (71.74%) or stage II (21.74%). The AKI group had higher renal tubular injury score and chronicity index (both p < .05). Binary logistic regression indicated that uric acid and baseline estimated glomerular filtration rate (eGFR) were independent risk factors for AKI in patients with IMN ( p < .05). The optimal cutoff value of serum uric acid for predicting AKI was 402.50 μmol/L and the baseline eGFR was 96.83 mL/min/1.73 m 2 . Kaplan–Meier's analysis showed that the cumulative renal survival rate was lower in the AKI group ( p = .047). Conclusions: AKI increases the risk of poor prognosis in IMN patients and the high uric acid and low baseline eGFR were considered independent predictors for developing AKI in patients with IMN.